Review of Surficial Geology and Engineering Hazards in the Canadian Offshore - Pelletier, Bernard (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1979)
Surficial geological mapping and hydrographic charting is most complete in the Atlantic Provinces offshore including the Gulf of St. Lawrence; secondarily, the British Columbia offshore and the Labrador Shelf and Slope are fairly well mapped and charted. However, the entire Arctic offshore has the poorest geological and hydrographic coverage of all Canadian marine waters, with the exceptions of Hudson Bay, Beaufort Sea-Amundsen Gulf area and Lancaster Sound. For safe marine operations, environmental information is required on winds, storms, waves, currents, tides and sea ice. This background is complemented by a seabed study designed to obtain grab and dredge samples of sediment or rock; to obtain sediment cores with the vibracorer, and gravity and piston corers; to obtain bedrock cores with the use of the diamond drill; to obtain bathymetric maps by means of sonic surveys in which echograms reveal the topographic profile of the sea-floor, and the side scan sonar give the area! view; to obtain details of bedrock features such as bedding, folds, faults, as well as distinguishing erosional and constructional topographic features all for the purposes of geological mapping; and to carry out visual surveys remotely or directly by means of submersible equipment and vehicles. All these background data and survey results can have direct application to seabed engineering problems. Potential hazards related to surficial geology in the Canadian offshore affect engineering operations such as drilling, dredging, dumping coastal works, foundations and anchorages, cable lays, and pipelines. These hazards are grouped into five main categories: (I) erosion and sedimentation, (2) Morphology, (S) movement, (4) ground ice, and (5) sediments. A breakdown is given as follows: ice-scour grooves and ridges, current scour and fill, buried river channels, sand waves, megaflutes, sand bars, valleys, fjords, canyons, troughs, thermokarst, pingos, mud diapirs, poakmarks, scarps, terraces, hummocky terrain, slump features, bedding dislocations, faulting, earthquakes, ice layers, ice-bonded sediments, thermal degradation, unstable substrate, hydrocarbons, organic matter, clathrates, hard (sand, boulders, bedrock) substrate, and moraine. The geologist must provide information and advice on the natural framework, and processes operating in the area; the engineer must appreciate these facts. But the engineer may be unable to re-locate his operational site; therefore, the geologist must present the information in its most complete and truest perspective in order to ensure a secure and successful operation.